Thermodynamic benchmark study using Biacore technology - Navratilova, Iva; Papalia, Giuseppe A.; Rich, Rebecca L.; Bedinger, Daniel; Brophy, Susan; Condon, Brad; Deng, Ta; Emerick, Anne W.; Guan, Hann-Wen; Hayden, Tanya; Heutmekers, Thomas; Hoorelbeke, Bart; et al. (Analytical biochemistry, 2007)
A total of 22 individuals participated in this benchmark study to characterize the thermodynamics of small-molecule inhibitor–enzyme interactions using Biacore instruments. Participants were provided with reagents (the enzyme carbonic anhydrase II, which was immobilized onto the sensor surface, and four sulfonamide-based inhibitors) and were instructed to collect response data from 6 to 36 °C. van’t Hoff enthalpies and entropies were calculated from the temperature dependence of the binding constants. The equilibrium dissociation and thermodynamic constants determined from the Biacore analysis matched the values determined using isothermal titration calorimetry. These results demonstrate that immobilization of the enzyme onto the sensor surface did not alter the thermodynamics of these interactions. This benchmark study also provides insights into the opportunities and challenges in carrying out thermodynamic studies using optical biosensors.